Study on the Association of the Polymorphism SLC2A9 rs6820230 with Gout in the Vietnamese Population - Ngoc, Nguyen Thy; Nhung, Vu Thi Hong; Ha, Do Thi Thu; Duong, Nguyen Thuy (VNU Journal of Science: Natural Sciences and Technology, 2025)
Gout is a metabolic disorder characterized by elevated uric acid levels in the blood, leading to joint inflammation and swelling in the limbs. Gout can be caused by various factors, with hereditary origins significantly contributing to the development of the disease. This study used the PCR-RFLP technique to determine the association between the SLC2A9 rs6820230 polymorphism and the risk of gout in the Vietnamese population. This study was conducted on a total of 477 samples, including 317 control samples and 160 gout samples. Statistical results show that the genotype distribution of the SLC2A9 rs6820230 polymorphism follows the Hardy-Weiberg equilibrium law with genotype frequency CC=88.49%; CT=14.47%; TT=1.05% and allele frequency C=0.917; T=0.083. In addition, we also determined that there is no association between the SLC2A9 rs6820230 polymorphism and the risk of gout in the Vietnamese population across five models, including additive, dominant, recessive, co-dominant and allelic. This study has provided more information about the influence of single nucleotide polymorphisms on the risk of gout in the Vietnamese population.